2021
DOI: 10.1097/md.0000000000026902
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis and incidence of hepatic encephalopathy of patients with liver cirrhosis treated with proton pump inhibitors

Abstract: Gastrointestinal bleeding, hepatic encephalopathy (HE), and hepatocarcinogenesis are associated with the prognosis of patients with liver cirrhosis (LC). Proton pump inhibitors (PPIs) have been used to prevent bleeding, however the effects of PPIs on overall survival have not yet been elucidated. Therefore, this multicenter retrospective study aimed to assess the effect of PPI on the prognosis and HE occurrence of the patients with liver cirrhosis in Japan.A total of 456 patients diagnosed with LC at the 4 ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to reports, PPI could increase the mortality of patients with liver cirrhosis and HE without active gastrointestinal bleeding [ 47 ]. However, a multicenter retrospective study found that for patients with cirrhosis, frequent treatment with PPI administration may increase the risk of HE incidence without worsening the prognosis of the patients [ 48 ]. In another single-center prospective study of 489 cirrhosis patients with or without acute-on-chronic liver failure, studied in subgroups with or without PPI therapy, it was found that PPI use did not increase mortality or the risk of HE in patients with cirrhosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, PPI could increase the mortality of patients with liver cirrhosis and HE without active gastrointestinal bleeding [ 47 ]. However, a multicenter retrospective study found that for patients with cirrhosis, frequent treatment with PPI administration may increase the risk of HE incidence without worsening the prognosis of the patients [ 48 ]. In another single-center prospective study of 489 cirrhosis patients with or without acute-on-chronic liver failure, studied in subgroups with or without PPI therapy, it was found that PPI use did not increase mortality or the risk of HE in patients with cirrhosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PPIs are associated with the development of HE (Table 2). 2,10,54,59–62 Several meta‐analyses have also confirmed a positive association between PPIs and the development of HE 66–70 . A recent meta‐analysis showed a pooled odds ratio (OR) and 95% confidence interval (CI) of 1.97 (1.51–2.58), suggesting an association between PPIs and HE 71 .…”
Section: Ppi and Cirrhosismentioning
confidence: 98%
“…11,12 Furthermore, because it remains difficult to find a consensus regarding the real side effects attributable to this class of drugs in the general population, the correct definition of these effects in patients with liver cirrhosis is even more complicated and the real effect of PPIs on cirrhotic patients remains controversial. [13][14][15][16][17] Considering that liver cirrhosis is per se a condition in which it is common to find alterations in the intestinal microbiome, anemia, encephalopathy, and a greater susceptibility to infections, it is necessary to clarify what is the impact of the use of PPIs in this group of patients. Relevantly, it would be important to clarify whether there is a concentration of PPIs intake that can be considered safe and if there is a correlation between the duration of PPIs intake and the onset of side effects or even if the different classes of PPIs have any effects on the outcomes.…”
Section: Effects Of Proton Pump Inhibitors In Cirrhotic Patients: Wha...mentioning
confidence: 99%